Penerapan Model Problem Based Learning Dipadu Tutorial Sebaya untuk Meningkatkan Hasil Belajar Siswa Kelas V SD - Marlina, Leni; Rokhmat, Joni; Fahrozi, Samsul (Darul Yasin Al Sys, 2023)
This article aims to explain conceptually about the use of PBL (Problem Based Learning) learning models in student activities and learning outcomes in elementary schools. This research is a classroom action research (PTK) that aims to improve students' mathematics learning outcomes by using the PBL (Problem Based Learning) model combined with peer tutorials. The subjects in this study were 22 Cakap class V students. In the initial condition, it shows the classical average value obtained is 36%. After being given action using the PBL (Problem Based Learning) learning model combined with the first cycle peer tutorial, the average grade was classically obtained at 55%. In cycle 2, the average completeness of student learning outcomes increased to 82%. These results show that there is an increase in student learning outcomes by using the PBL (Problem Based Learning) learning model combined with Peer Tutorials, so it can be concluded that PBL (Problem Based Learning) Combined with Peer Tutorials can improve the mathematics learning outcomes of Kela V Saucy students of SDN 23 Ampenan.